Analysis of Voltage Drop and Power Loss Calculations inthe Edelweiss Feeder of PT PLN (Persero) Abepura Customer Service Unit - Ekawati Margaretha Ohee; Dultudes Mangopo; Suparno; Oktavianus Kati; Rombe Allo; Semuel Boron Membala; Allo Sarira Pongsapan (Jurnal ASIIMETRIK Jurnal Ilmiah Rekayasa & Inovasi, 2026)
This study evaluates the performance of the 20 kV Edelweiss feeder by analysing transformer loading, voltage drop, and technical power losses in a radial distribution network. The analysis is based on a bus-by-bus electrical model derived from feeder topology, conductor impedance, load current, power factor, and segment length data. Voltage profiles and technical losses are quantified using established three-phase power flow relationships based on Ohm’s law and Kirchhoff’s current law, enabling the assessment of cumulative voltage drop and loss propagation along the feeder. The results show that the feeder maintains a highly stable voltage profile, with a total voltage drop of 41.422 V, equivalent to approximately 0.207% of the nominal 20 kV voltage. Total active and reactive power losses are 7.3103 kW and 4.7821 kVAR, respectively, with more than 96% of these losses concentrated in Bus 2 and Bus 3. The findings demonstrate that technical losses are governed primarily by current accumulation, electrical distance, and topological position within the radial network rather than by conductor length alone. This study contributes a feeder-level understanding of how upstream current aggregation shapes voltage-drop and loss distribution, providing empirical evidence for identifying critical segments in medium-voltage radial distribution systems .